2002
DOI: 10.1074/jbc.c200536200
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination-independent Trafficking of G Protein-coupled Receptors to Lysosomes

Abstract: Ubiquitination of cytoplasmic lysine residues can target G protein-coupled receptors (GPCRs) to proteasomes and has recently been shown to also be required for sorting of certain GPCRs to lysosomes following ligand-induced endocytosis. We addressed the generality of this mechanism by examining regulated proteolysis of the murine ␦ opioid receptor (DOR) expressed in human embryonic kidney 293 cells, a well characterized model system in which receptors are sorted to lysosomes. Incubation of cells in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
115
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 35 publications
8
115
0
Order By: Relevance
“…7C). Although MG132 is a highly potent inhibitor of a number of proteasome-associated proteases, this compound is not specific for proteasomes and also potently inhibits various cysteine proteases and cathepsins (25). These results suggest that sst 2A and sst 3 undergo differential endosomal sorting.…”
Section: Resultsmentioning
confidence: 68%
“…7C). Although MG132 is a highly potent inhibitor of a number of proteasome-associated proteases, this compound is not specific for proteasomes and also potently inhibits various cysteine proteases and cathepsins (25). These results suggest that sst 2A and sst 3 undergo differential endosomal sorting.…”
Section: Resultsmentioning
confidence: 68%
“…Proteasomal inhibitors are reported to either reduce (12) or have no effect (17) on agonist-mediated internalization and degradation of ␤ 2 AR. In one study proteasomal but not lysosomal inhibitors reduced the down-regulation of and ␦ opioid receptors (14), whereas in another, lactacystin, a very specific proteasomal inhibitor, did not impair agonist-induced internalization, lysosomal targeting, and degradation of the ␦ opioid receptor (15). Some of these studies found that steadystate receptor levels increase in unstimulated cells treated with proteasomal inhibitors (14,17).…”
mentioning
confidence: 96%
“…14, but see Ref. 15), and the vasopressin V2 receptor (16). Eliminating receptor ubiquitination reduces agonist-mediated receptor degradation but not internalization.…”
mentioning
confidence: 99%
“…The trafficking of G protein-coupled receptors (GPCRs) 1 appears to be largely mediated by phosphorylation and/or ubiquitination of their intracellular domains (1)(2)(3)(4)(5) and/or by their association with trafficking proteins such as the non-visual arrestins (6,7), N-ethylmaleimide-sensitive factor (8), ezrin-radixinmoesin-binding phosphoprotein-50/sodium-hydrogen exchange regulatory factor (EBP50/NHERF, see Ref. 4), sorting nexins (9), or GPCR-associated sorting protein (see Ref.…”
mentioning
confidence: 99%